2014
DOI: 10.1107/s1399004714013844
|View full text |Cite
|
Sign up to set email alerts
|

Expression, crystal structure and cellulase activity of the thermostable cellobiohydrolase Cel7A from the fungusHumicola griseavar.thermoidea

Abstract: Cellobiohydrolase Cel7A from H. grisea var. thermoidea showed a 10°C higher T m and a 75% higher yield than H. jecorina Cel7A in a performance assay at 65°C. The crystal structure at 1.8 Å resolution indicates higher flexibility in tunnel-defining loops and reveals a new loop conformation near the active centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…Regarding the former, Grassick et al () reported that the B2 loop of Re Cel7A (in which the current mutations are made) was flexible to the extent that the loop was not visible in the electron density map and this obviously speak against strong A3–B2 loop interactions in the unligated form. A high degree of fluctuation of the B2 loop has also been reported in Hg Cel7A (Momeni et al, ) and Hi Cel7A (Momeni et al, ). One possible joint interpretation of this structural and kinetic information is that the B2 loop engages in interactions with the substrate and the A3 loop late in the association path, when the transition state of this process has been passed and the cellulose strand is gradually filling the binding tunnel.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Regarding the former, Grassick et al () reported that the B2 loop of Re Cel7A (in which the current mutations are made) was flexible to the extent that the loop was not visible in the electron density map and this obviously speak against strong A3–B2 loop interactions in the unligated form. A high degree of fluctuation of the B2 loop has also been reported in Hg Cel7A (Momeni et al, ) and Hi Cel7A (Momeni et al, ). One possible joint interpretation of this structural and kinetic information is that the B2 loop engages in interactions with the substrate and the A3 loop late in the association path, when the transition state of this process has been passed and the cellulose strand is gradually filling the binding tunnel.…”
Section: Discussionmentioning
confidence: 60%
“…Conversely, Cel7D from Phanerochaete chrysosporium ( Pc Cel7D), which is also a processive cellobiohydrolase, has a number of loop deletions and hence much more accessible substrate binding region (Munoz et al, ). Other fungal Cel7As, including enzymes from Hypocrea hazianum ( Hz Cel7A) (Textor et al, ), Humicola grisea ( Hg Cel7A) (Momeni et al, ), and Heterobasidion irregulare ( Hi Cel7A) (Momeni et al, ) have intermediate degrees of tunnel coverage and loop fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…RemCel7A, Melanocarpus albomyces Cel7B, Humicola grisea var. thermoidea Cel7A, and A. fumigatus Cel7A [22,24,49,50]. As a result, the GcaCel7A ligand fluctuates slightly more than that of HjeCel7A in the À7 and À6 sites (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Three-dimensional structures of the catalytic domains of nine GH7 CBHs have been published previously, the first being HjeCel7A and the most recent being Aspergillus fumigatus Cel7A [19][20][21][22][23][24][25][26][27]. The structures share a common b-jelly roll fold with a curved b-sandwich constructed from two largely antiparallel b-sheets packing face-to-face, forming an approximately 50-A-long substrate-binding groove along the GH7 catalytic module.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of CBH-1 from a number of filamentous fungi shows an N-terminal pGlu modification (20, 21). The crystal structures of additional GH7 members, including EG1 (Cel7b) (22, 23) and Cel7D (24) have an N-terminal pGlu.…”
Section: Resultsmentioning
confidence: 99%